Development of a nested real time PCR/high resolution melting assay for human T-cell lymphotropic viruses types 1 and 2 (HTLV-1 and 2) identification - Caputo, Mariela (2022)
HTLV-1 and HTLV-2 are present in different high-risk populations, such as sexual workers and injecting drug users (IDUs). HTLV-1 is endemic in areas of Middle East, Southern Japan and Latin America, whereas HTLV-2 infection is endemic among some Native Americans and some Central African tribes. The pathogenic consequences and clinical manifestations of these two viruses differ significantly, demanding an adequate identification; therefore, proper diagnosis of HTLV-1 and 2 infection is crucial. To get a final diagnosis of HTLV-1 or 2 infection, it is recommended that positive serologic samples should be confirmed by PCR assays or western blot (WB) analysis. Thus, the aim of this study was to develop and implement a simple reaction for the rapid identification of HTLV-1 and 2. Nested real-time PCR technique followed by high resolution melting was performed based on the tax/rex sequences of HTLV-1 (M2) and HTLV-2 (MoT) cell lines perfectly discriminating between HTLV-1 from HTLV-2, by distinct melting curve profiles. The sensitivity assay of this method revealed that at least 1 viral copy of HTLV-1 or 1·5 viral copy of HTLV-2 could be amplified. Later, this method was validated using 200 blood samples from corpses. In agreement with previous epidemiological, the HTLV-1 and 2 prevalence was 1·5% (CI 95%: 0·31–4·3) and 0·5% (CI 95%: 0·013–2·75), respectively. The strategy proposed herein has some advantages over other PCR-based tests because it not only reduces considerably time and the costs of the total diagnosis but also allows detection and discrimination of HTLV-1 and 2 in the same reaction.